Diabetes prevention education program for community health care workers in Thailand - Kitti Sranacharoenpong (2018)
To evaluate the effects of a 4-month training program on the knowledge of CHCWs. CHCWs from 69 communities in Chiang Mai province in Thailand were assigned to the intervention group (IG, n = 35) or control group (CG, n = 34). All CHCWs were assessed for knowledge at baseline and at 4-months. The intervention group received a training program of 16 sessions of 2.5 h each within a 4-month period. A mix of classroom and E-learning approaches was used. All CHCWs were assessed for knowledge at baseline, 4-month, and follow-up at 8-month. Assessment was based on a pretested examination addressing understanding of nutritional terms and recommendations, knowledge of food sources related to diabetes prevention and diet-disease associations. Overall, the knowledge at baseline of both groups was not significantly different and all CHCWs scored lower than the 70% (mean (SD), 56.5% (6.26) for IG and 54.9% (6.98) for CG). After 4-month, CHCWs in the IG demonstrated improvement in total scores from baseline to 75.5% (6.01), P < .001 and relative to the CG 57.4% (5.59), P < .001. The follow up phase at 8-month, IG were higher in total scores than CG (71.3% (7.36) and 62.4% (6.81), P < .001). The diabetes prevention education program was effective in improving CHCWs' health knowledge relevant to diabetes prevention. The innovative learning model has potential to expand chronic disease prevention training of CHCWs to other parts of Thailand. © Springer Science+Business Media, LLC 2012.